EVOLUTION OF SOCIAL INSTITUTIONALIZATION OF THE UNIVERSITY - Радіонова, Людмила; Козирєва, Наталія (SWorldJournal, 2024)
The article compares the points of view on the mission and role of the university of the classics of social philosophy. The principles of development of the classical university are analysed, on the basis of which such categories as sustainability, stabi